Pemanfaatan QGIS Sebagai Media Pembelajaran Geospasial Untuk Meningkatkan Kemampuan Berpikir Spasial Siswa - Ariani Ariani; Sunarty Suly Eraku; Sri Maryati (Universitas Negeri Gorontalo, 2026)
The community service activity was conducted to strengthen students spatial thinking skills through QGIS-based geospatial learning at SMA Negeri 1 Lakea. The problem addressed was the limited experience of grade X students in producing digital maps using Geographic Information System software. The activity used short lectures, demonstrations, guided practice, discussion, and evaluation through pre-test, post-test, observation, map product assessment, and student response questionnaires. Twenty-five students participated in the training. The results showed a substantial improvement in students understanding and basic skills, indicated by an increase in the average score from 32 in the pre-test to 97.2 in the post-test. Students were able to add layers, read attributes, symbolize data, and compose simple map layouts with guidance. QGIS also encouraged students to understand location, distance, direction, pattern, distribution, and spatial relationships. This activity is important as a practical model for integrating open-source geospatial technology into geography learning.